ATRIBUTOS QUÍMICOS DO SOLO, TROCAS GASOSAS E PRODUÇÃO DE FAVA (Phaseolus lunatus L.) SUBMETIDA À INOCULAÇÃO E A DIFERENTES FONTES DE ADUBAÇÃO - Mariano, Elisângela de Freitas (2019)
The lima-bean (Phaseolus lunatus L.) is a food plant species of socioeconomic importance for the Northeast region of Brazil. However, few studies analyze its behavior according to alternative nutritional sources. Thus, the objective of this study was to evaluate the chemical attributes of the soil production and gas exchange of the bean subjected to inoculation and different sources of fertilization. The experiment was conducted at the Agriculture Sector of the Center for Social and Agrarian Human Sciences (CCHSA) of the Federal University of Paraíba (UFPB), Campus III, in the municipality of Bananeiras - PB. The experimental design was a randomized block with three replications, in a 2 x 10 factorial arrangement, with two bean genotypes (Branca and Rajada) and ten treatments. The plants were submitted to the following treatments: control (T1), mineral fertilization (T2), organic fertilization (T3), inoculation (T4), biostimulant (T5), inoculation + ½ of mineral fertilization (T6), inoculation + organic fertilization ( T7), biostimulant + inoculation (T8), biostimulant + mineral fertilizer (T9) and biostimulant + organic fertilizer (T10). During the flowering period, the variables related to gas exchange were analyzed. During the harvest period the production variables were analyzed. At the end of the experiment soil samples were collected to evaluate the chemical properties of the soil cultivated with the squash bean and the associated biomass production. Data were subjected to analysis of variance at 5% probability by the F test. Plants submitted to alternative nutrient sources were more efficient in WUE, Wleaf and E. The highest yield of bean was obtained in plants subjected to inoculation. to organic fertilization, mineral fertilization, mineral fertilization + inoculation and biostimulant + organic fertilization. The Rajada bean presented greater pod length per plant and a mass of one hundred grains. Organic fertilization promoted an increase in fava bean biomass, while promoting an increase in the chemical attributes of the soil through P and K. Alternative sources of fertilization may integrate the nutritional management of fava bean culture in the Northeast region of Brazil.